Meningkatkan Prestasi Belajar PKn Melalui Metode Pembelajaran Kooperatif Model Gabungan Ceramah Dan Sumbang Saran Pada Siswa Kelas IV SDN 002 Rambah - Abdul Aziz (STKIP ROKANIA, 2018)
This study aims to improve student achievement PKn students by using cooperatif learning model combined and brainstroming suggestions. This type of research is action research using three cycles. The subject of research that is the class IV SDN 002 Rambah. The result of the study showed that student learning increased from cycle I (70,0%), cycle II (77,7%), cycle III (92,0%). Based on the result and analysis of the study concluded that cooperative learning method of combined model of lectures and brains stroming can improve students learning achievement